Justice and the Pandemic City: How the Pandemic Has Revealed Social, Urban, and Data Injustices, and How a Narrative Approach Can Unlock Them - Gulsrud, Natalie Marie; Steiner, Henriette (Frontiers in Sustainable Cities, 2022)
The global COVID-19 pandemic has exacerbated infrastructural, societal, and resource inequalities along racial and socioeconomic lines. Many countries have struggled to provide adequate COVID testing and healthcare. Denmark has been exceptional in its investment in a hyper-efficient and ever-present infrastructure, with testing tents distributed across the country. In this article we ask: What is the impact of this infrastructure in terms of the (urban) culture that is built around testing? And what does that mean in terms of data management and mass surveillance? As a public good, the COVID-19 testing infrastructure has costs and benefits, but these are not always clear. They concern future urban life and data management, and our ability to draw a boundary around ourselves—that is, biopolitics. At the time of writing, with the Omicron variant on the rise, we are hovering on the threshold between new restrictions and a post-COVID urban reality. Now is the time to take stock of the COVID infrastructure’s spatial, temporal, and political dimensions, and of what they mean for urban decision-making, governance, justice, and democracy. To do so, and following philosopher and legal scholar Martha Nussbaum, we suggest the deployment of a narrative approach for the education of democratic citizenship and, indeed, for justice.